2020
DOI: 10.1111/scd.12449
|View full text |Cite
|
Sign up to set email alerts
|

Using the web to increase access to oral health care for patients with special health care needs in South Carolina: A replicable model

Abstract: Aim To create an accessible web‐based resource of providers willing to provide dental services for patients with special health care needs (SCHNs). Methods With a grant from The Duke Endowment, surveys were sent to dentists in South Carolina Results Data showed that the majority of providers expressed willingness to treat patients with one or more mild SHCN, but fewer expressed willingness to treat those with one or more moderate or severe SHCN. Additionally, the data showed that among general practitioners sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…Surprisingly, neither payer status nor medical/behavioral accommodation status significantly affected the outcome of having a visit with a new dentist in this study, despite perceived barriers among our survey respondents and other studies of not being able to find a dentist who understands the individual's SHCN and accepts their insurance 11,29,30 …”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Surprisingly, neither payer status nor medical/behavioral accommodation status significantly affected the outcome of having a visit with a new dentist in this study, despite perceived barriers among our survey respondents and other studies of not being able to find a dentist who understands the individual's SHCN and accepts their insurance 11,29,30 …”
Section: Discussioncontrasting
confidence: 78%
“…Surprisingly, neither payer status nor medical/behavioral accommodation status significantly affected the outcome of having a visit with a new dentist in this study, despite perceived barriers among our survey respondents and other studies of not being able to find a dentist who understands the individual's SHCN and accepts their insurance. 11,29,30 Minimal standards for dental education in SHCN have been cited as a barrier to transitioning to adult care for patients with SHCN 13,31,32 Studies have found that dentists who reported having hands-on and didactic experiences during dental school were more likely to treat children with SHCN and that dentists who reported more opportunities to treat patients with complex needs in dental school treat significantly more of these patient populations in their practices, including patients who are medically compromised, frail elders, and those with developmental disabilities. 33,34 However, there was no difference in willingness between those with or without postgraduate training in a General Practice Residency (GPR) or Advanced Education in General Dentistry (AEGD), suggesting that advanced education alone may not solve this complex access problem.…”
Section: Barriersmentioning
confidence: 99%